A direct analytical predetermination of PMSG based WPS steady-state values under different operating conditions. Issue 5 (October 2022) - Vijayapriya, Ramachandran; Raja, Pitchaimuthu; Selvan, Manickavasagam Parvathy
This paper presents a direct analytical method to predetermine the steady-state values of a permanent magnet synchronous generator (PMSG) based wind power system (WPS) at each stage of power flow. A generalized structured is developed with two independent equivalent circuits, that is, PMSG and grid side. To effectively determine the converters performance numerals despite grid disturbances, steady-state model is structured with positive sequence components of grid voltage. The advantage of the proposed model is that the methods evade the requirements of d-q modeling and a dedicated controller to evaluate the system performance. Using the proposed steady-state model, the entire WPS components ratings is predicted evading time domain simulation with complicated controller design. Also, the simple controller design is proposed to aid in optimal power flow supplement with FRT requirements under all possible system operating conditions. Ultimately, validation of predetermined values with the simulated PSCAD/EMTDC response including the proposed controller is investigated.